(untitled) (Interdisciplinary Journal of Nursing and Health, 2022)
With increasing life expectancy, the share of older persons with coexisting multiple chronic degenerative diseases (comorbidity / multimorbidity) is expanding. These conditions require the use of multiple drugs, leading to polypharmacy, which plays a central role in making the therapeutic approach to the elderly particularly complex, together with age-related changes in pharmacokinetics and pharmacodynamics. Physicians and nurses both are challenged by polypharmacy and by the other drug-related issues involving older patients, in all care settings. In particular, nurses should be aware of the main issues of pharmacotherapy in older persons, because they are often the frontline for older patients care, especially in nursing homes. This review addresses the main issues related to pharmacotherapy in late life, such as pharmacokinetics and pharmacodynamics changes, limitations of evidence-based medicine, polypharmacy, drug interactions, adverse drug reactions, and lack of adherence. Focus will be on how these problems may impact on nursing, and on what nurses should know and do to improve drug treatment of older patients. In the last decade, the role and responsibilities of nurses in the management of drug therapy have significantly changed in most countries. There is consensus in educational programs and legislation that the preparation and administration of medications are essential aspects of nursing practice. These are considered as collaborative tasks with physicians and not purely mechanistic tasks. The nurse must intervene in the event of a perceived error, and he/she must report doubts about congruity or relevance of the therapy. Although nursing students gain knowledge and develop skills on drug therapy during their education, these are often perceived as insufficient. The need for post-graduation continuing education should be also emphasized. Thus, graduate and post-graduate educational programs should be developed, in order to offer adequate answers to the increasing and challenging share of older patients seen in clinical practice.